PC-Based Real Time Data Processing System for Doppler Sodar Applications - Sreedevi, D; Raju, DSSN; Hareesh Babu, M; Purnachandra Rao, M; Ramana Murty, NV (International Journal of Computer Sciences and Engineering, 2025)
SODAR, an acoustic pulse radar, provides detailed information on dynamic properties of air turbulence in the lower part of the atmosphere. The speed of the transmitted sound wave is responsive to changes in wind swift, due to high rate of susceptibility to temperature variations. The velocity of the transmitted sound wave propagation is much lower when comparing to velocity of electromagnetic waves. Due to this fact the processing of sodar information is significantly simplified and reached better spatial resolution and dead zone. Sophisticated model of tri-static sodar has developed to using general purpose PC to study the properties of sound wave at see breeze.